2020
DOI: 10.1186/s12877-020-1425-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between complex multimorbidity, activities of daily living and mortality among older Norwegians. A prospective cohort study: the HUNT Study, Norway

Abstract: Background: With increasing age, having multiple chronic conditions is the norm. It is of importance to study how coexistence of diseases affects functioning and mortality among older persons. Complex multimorbidity may be defined as three or more conditions affecting at least three different organ systems. The aim of this study was to investigate how complex multimorbidity affects activities of daily living and mortality amongst older Norwegians. Methods: Participants were 60-69-year-olds at baseline in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 53 publications
5
45
0
Order By: Relevance
“…Furthermore, requiring these multiple conditions to be present in separate body systems identifies multimorbidity that is likely to require care from several specialists, which has been termed complex multimorbidity [20]. Such complex multimorbidity presented a moderate relationship with mortality, adjusted for sociodemographic characteristics, in a study on individuals aged 60 to 69 years in Norway [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, requiring these multiple conditions to be present in separate body systems identifies multimorbidity that is likely to require care from several specialists, which has been termed complex multimorbidity [20]. Such complex multimorbidity presented a moderate relationship with mortality, adjusted for sociodemographic characteristics, in a study on individuals aged 60 to 69 years in Norway [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we derived a three-category variable to capture multimorbidity (‘no multimorbidity’ = 0–1 conditions; ‘simple multimorbidity’ = 2–3 conditions; and ‘complex multimorbidity’ = 4 + conditions). Previous research has shown that differentiating between simple and complex multimorbidity can better capture the variability in multimorbidity in older adults 28 , 29 . ADLs 30 included walking across the room, dressing, bathing and showering, eating, and getting in and out of bed.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it estimates direct effects mediated by other factors that integrate the causal network of outcomes of interest (10)(11) . Thus, given the results of the studies with this theme (1,(3)(4)(5)(6)(7)(8)(9) , it is assumed that functional disability results from sociodemographic, economic, clinical and behavioral characteristics of the older adult. However, there are doubts about which of these factors act directly or through mediation.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis, it was observed that low physical performance and reduction of strength and muscle mass were associated with functional dependence ( 8 ) . It is noteworthy that, in a cohort in Norway, older adults with complex comorbidities have higher risks of dependence in the ADLs and of mortality ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%